Metallic Nanoparticle-Based Optical Cell Chip for Nondestructive Monitoring of Intra/Extracellular Signals - Sang-Nam Lee; Jin-Ha Choi; Hyeon-Yeol Cho; Jeong-Woo Choi (MDPI AG, 2020)
The biosensing platform is noteworthy for high sensitivity and precise detection of target analytes, which are related to the status of cells or specific diseases. The modification of the transducers with metallic nanoparticles (MNPs) has attracted attention owing to excellent features such as improved sensitivity and selectivity. Moreover, the incorporation of MNPs into biosensing systems may increase the speed and the capability of the biosensors. In this review, we introduce the current progress of the developed cell-based biosensors, cell chip, based on the unique physiochemical features of MNPs. Mainly, we focus on optical intra/extracellular biosensing methods, including fluorescence, localized surface plasmon resonance (LSPR), and surface-enhanced Raman spectroscopy (SERS) based on the coupling of MNPs. We believe that the topics discussed here are useful and able to provide a guideline in the development of new MNP-based cell chip platforms for pharmaceutical applications such as drug screening and toxicological tests in the near future.